Industrial Ecology in Practice: opportunities and limitations for the installation of an ecological crushed stone industry in Rio Grande/RS - Alves, Ana Paula Ferreira; Trevisan, Marcelo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Aiming to achieve a balance between economic growth and the nature preservation, emerged the concept of industrial ecology (IE), with the fundamental perspective of nature as a model by integrating ecological and industrial systems. Thus, residues from a production process can be used as raw material for other products manufacture. Particularly, the ecological crushed stone is a product considered environmentally friendly, because it is an alternative to the proper treatment of waste from one sector (footwear industry) in another economic activity (construction).The construction sector could cause major environmental impacts by the use of natural resources and the waste generation. In this context, this research aims to analyze the opportunities and limitations of the possibility of installing ecological crushed stone industry in Rio Grande. To do so, we conducted interviews with potential suppliers, customers and competitors. The results show that there is interest in selling the product, taking into account the increasing need to reduce consumption and extraction from natural sources. However, there is public resistance to using innovative products targeted to the sector, the lack of knowledge about ecological crushed stone characteristics and constraints involving the amount of waste and the condition for its supply.